2020
DOI: 10.1007/s13205-020-02427-7
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrozingerone protects temozolomide-induced cognitive impairment in normal and C6 glioma rats besides enhancing its anticancer potential

Abstract: Considering the cognitive impairment induced by temozolomide (TMZ) in glioblastoma survivors, the present study was aimed to evaluate the protective effect of dehydrozingerone (DHZ) against TMZ-induced cognitive impairment (chemobrain) and C6 cell line-induced glioma in male Wistar rats. In both chemobrain and glioma models, TMZ was administered at a dose of 18 mg/kg i.v every 5th day and DHZ at a dose of 100 mg/kg p.o. daily. Additionally, glioma was induced by intracerebral injection of 5 × 104 C6 rat glioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…In general, some architectural disturbances and insulted neurons were seen in the hematoxylin and eosin slides of the hippocampus of temozolomide and temozolomide + l -Dopa 25 mg/kg groups. Although this finding is in accordance with the results of our behavioral and molecular tests, histologically, as Pathak et al . (2020) showed, the differences between temozolomide and other groups appear to be negligible.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In general, some architectural disturbances and insulted neurons were seen in the hematoxylin and eosin slides of the hippocampus of temozolomide and temozolomide + l -Dopa 25 mg/kg groups. Although this finding is in accordance with the results of our behavioral and molecular tests, histologically, as Pathak et al . (2020) showed, the differences between temozolomide and other groups appear to be negligible.…”
Section: Discussionsupporting
confidence: 94%
“…Temozolomide by different protocols, mediates learning and memory impairments. Pathak et al . (2020), in one of these studies, showed temozolomide-treated rats explore novel objects less than familiar ones.…”
Section: Discussionmentioning
confidence: 99%
“…Male Wistar rats treated with TMZ (18 mg/kg, i.v) once in 5 days over 32 days showed no preference to the novel object in NORT. The antioxidant analysis showed that TMZ increased MDA and reduced SOD and catalase levels compared with the control group animals (Pathak et al 2020).…”
Section: Temozolomidementioning
confidence: 84%
“…Anti-oxidant parameters like catalase, superoxide dismutase (SOD), GSH lipid peroxidation, and total protein were estimated in the liver tissue (Pathak et al 2020 ), using routine laboratory UV spectroscopic and calorimetric methods.…”
Section: Methodsmentioning
confidence: 99%